Modeling and Control of 5DOF Robot Arm Using Fuzzy Logic Supervisory Control - Mohammad Amin Rashidifar; Ali Amin Rashidifar; Darvish Ahmadi (IAES International Journal of Robotics and Automation (IJRA), 2013)
Modeling and control of 5 degree of freedom (DOF) robot arm is the subject of this article. The modeling problem is necessary before applying control techniques to guarantee the execution of any task according to a desired input with minimum error. Deriving both forward and inverse kinematics is an important step in robot modeling based on the Denavit Hartenberg (DH) representation. Proportional integral derivative (PID) controller is used as a reference benchmark to compare its results with fuzzy logic controller (FLC) and fuzzy supervisory controller (FSC) results. FLC is applied as a second controller because of the nonlinearity in the robot manipulators. We compare the result of the PID controller and FLC results in terms of time response specifications. FSC is a hybrid between the previous two controllers. The FSC is used for tuning PID gains since PID alone performs not satisfactory in nonlinear systems. Hence, comparison of tuning of PID parameters is utilized using classical method and FSC method. Based on simulation results, FLC gives better results than classical PID controller in terms of time response and FSC is better than classical methods such as Ziegler-Nichols (ZN) in tuning PID parameters in terms of time response.